An Analysis Of Students’ Ability In Writing Descriptive Text - Magama, Eklesya Glori; Liando, Nihta V.F; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
English as a foreign language is important language that must be learned for students to communicate with teachers, friends or even another person from a various country. the researcher is interested to focusing the research in analyzing the student ability and difficulties in writing especially in descriptive text. In this research, the researcher used Qualitative methods in analyzing student writing for descriptive texts involve collecting and analyzing non-numerical data to understand how students write and describe objects, places, or people. the subject matter in writing descriptive language were rated as good. The students' mean score for topic of sentence was 80,1 or good. Although they did not do an excellent job, the pupils did not do a terrible job of elaborating the offered topic. They were unsure of how to write and communicate their views. The students' mean score in sentence description was 70,4, which is considered ordinary. The students ability in develop of paragraph still lack, it become students had less of vocabularies. And the students' mean score in conclusion of sentence was 61,3 also classified as average. The students not know to summarizes main ideas every paragraph. And the students mean score was 70.6 which was classified as good